1987
DOI: 10.1111/j.1365-2591.1987.tb00593.x
|View full text |Cite
|
Sign up to set email alerts
|

Pulpal response to a zinc oxide–eugenol cement

Abstract: Summary. The British Standards Institution have produced a recommended testing procedure for toxicity of dental materials; this advocates the use of a zinc oxide—eugenol cement such as Kalzinol, as a bland control in deep cavities. In this study, Kalzinol was applied directly to the exposed pulps of germ‐free rat molar teeth. This resulted in pulpal inflammation in contact with the material; when dentine particles separated Kalzinol from the pulp, calcific repair tissue was observed without inflammation or ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
2
1

Year Published

1989
1989
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 16 publications
2
12
2
1
Order By: Relevance
“…They used MTA for base material in laser pulpotomy to provide superior sealing ability while preventing the tissue-damaging effects of zinc oxide eugenol. Placement of eugenol in direct contact with vital tissue initiates a moderate to severe inflammatory response with resulting chronic inflammation and necrosis (16). They found all the teeth of each group clinically successful at each follow-up visit, and there were no statistically significant differences between both groups with regard to radiologic success criteria, whereas the radiologic success rate of L-MTA (70.8%) was lower than that of zinc oxide eugenol sealing (87.5%).…”
Section: Discussionmentioning
confidence: 58%
“…They used MTA for base material in laser pulpotomy to provide superior sealing ability while preventing the tissue-damaging effects of zinc oxide eugenol. Placement of eugenol in direct contact with vital tissue initiates a moderate to severe inflammatory response with resulting chronic inflammation and necrosis (16). They found all the teeth of each group clinically successful at each follow-up visit, and there were no statistically significant differences between both groups with regard to radiologic success criteria, whereas the radiologic success rate of L-MTA (70.8%) was lower than that of zinc oxide eugenol sealing (87.5%).…”
Section: Discussionmentioning
confidence: 58%
“…Watts and Paterson (57) suggested that ZOE can cause pulp inflammation with a risk of subsequent internal resorption when used as a base for pulpotomies. In line with this suggestion, the placement of ZOE directly over the pulp tissue may explain the instances of internal resorption that have previously been reported in FS pulpotomies (26,27).…”
Section: Clinical Research Discussionmentioning
confidence: 99%
“…Di¡erent animal species have been recommended for use in pulp or dentine tests in order to evaluate the biocompatibility of experimental dental materials (ISO DIS 74051994). Although most of these tests have been carried out in nonhuman primate teeth, many workers have used the teeth of rats or ferrets as experimental models for evaluation of the response of pulps to dental materials (Wennberg et al 1983, Watts & Paterson 1987, Tsuneda et al 1995, Hayashi et al 1999, Costa et al 2000b, Six et al 2000. The relatively high costs of in vivo studies using animals such as nonhuman primates have led to the use of small animal species such as rats.…”
Section: Discussionmentioning
confidence: 99%